Genetic Analysis of in Korean Patients Associated with Atrioventricular Conduction Block - Hyoung Seob Park; Yoon Nyun Kim; Young Soo Lee; Byung Chun Jung; Sang Hee Lee; Dong Gu Shin; Yongkeun Cho; Myung Hwan Bae; Sang Mi Han; Myung Hoon Lee (Genomics & Informatics)
Recent several studies have shown that the genetic variation of SCN5A is related with atrioventricular conduction block (AVB); no study has yet been published in Koreans. Therefore, to determine the AVB-associated genetic variation in Korean patients, we investigated the genetic variation of SCN5A in Korean patients with AVB and compared with normal control subjects. We enrolled 113 patients with AVB and 80 normal controls with no cardiac symptoms. DNA was isolated from the peripheral blood, and all exons (exon 2-exon 28) except the untranslated region and exon-intron boundaries of the SCN5A gene were amplified by multiplex PCR and directly sequenced using an ABI PRISM 3100 Genetic Analyzer. When a variation was discovered in genomic DNA from AVB patients, we confirmed whether the same variation existed in the control genomic DNA. In the present study, a total of 7 genetic variations were detected in 113 AVB patients. Of the 7 variations, 5 (G87A-A29A, intervening sequence 9-3C>A, A1673G-H558R, G3578A-R1193Q, and T5457C-D1819D) have been reported in previous studies, and 2 (C48G-F16L and G3048A-T1016T) were novel variations that have not been reported. The 2 newly discovered variations were not found in the 80 normal controls. In addition, G298S, G514C, P1008S, G1406R, and D1595N, identified in other ethnic populations, were not detected in this study. We found 2 novel genetic variations in the SCN5A gene in Korean patients with AVB. However, further functional study might be needed.